Mekanisme Pasar dalam Pandangan Yahya bin Umar - Faried KR; Abd. Muiz al-Kiram; Nurizal Ismail (Mumtaz Publishing, 2023)
The market mechanism is the tendency for supply and demand to equilibrate (i.e., prices move to the market-clearing level), so that there is neither excess demand nor excess supply, as introduced by Adam Smith (1729-1790) and later developed by the classical economists. In the literature of the history of Islamic economic thought, there have been many studies related to the issue of market mechanisms. Al-Ghazāli and Ibn Taimiyah argued that prices can influence the quantity demanded and supplied. Yahya bin Umar (828-901 AD) also discussed market mechanisms in his book Ahkām Assūq, which is the earliest work examining economic thought on hisbah. Therefore, this study aims to understand the market mechanism according to Yahya bin Umar's views as presented in his work Ahkām Assūq. The research methodology employed is a qualitative approach using literature review and content analysis. The findings of this study state that Yahya bin Umar's perspective on the market mechanism is the process of the intersection between demand and supply, which then determines the prices and volume of desired goods through the decree of Allah Swt.